Stigmatized and Damaged: Public Health Challenges from Stigmatization to Disinformation: A Review of Shanghai University Presentation - Liu, Haoyi; Liu, Shiyu (The Journal of Medicine, Humanity and Media, 2025)
On the afternoon of July 9, 2025, the 8th "Medicine, Humanity and Media" Health Communication International Conference & PhD Symposium:Shanghai University Presentation: Stigmatized and Damaged: Public Health Challenges from Stigmatization to Disinformation was held at Peking University. The presentation was led by Associate Professor He Qijun of Shanghai University, who, together with three doctoral students, reported on disease stigma and social context, the impact of naming type and picture type on public stigma in Alzheimer’s disease, identity dilemma and coping strategies of elderly male AIDS patients, and the threat of disinformation posed by AI-generated in-depth falsified content for health, respectively. Chen Hongliang, a Research Fellow at Zhejiang University, as a reviewer affirmed the research and made suggestions, and Professor Xu Jing of Peking University expressed her sincere gratitude to all the presenters and participants.